Nurses’ view of the nature of the support given to parents in the neonatal intensive care unit - Sidek, Syazwana Mohd.; Marup, Sofiah; Zolkefli, Yusrita (Belitung Raya Foundation, Indonesia, 2021)
Background: Most parents of Neonatal intensive care unit (NICU) babies often expressed dissatisfaction with the nursing care in NICU because of their unaddressed needs, resulting in emotional strain. This raises an essential question of how NICU nurses provide support for the parents. However, this can be relatively challenging in the NICU setting. Objective: To explore nurses’ views on the nature of parental support provided in NICU settings in Brunei Darussalam. Methods: This study employed a qualitative research approach conducted in 2020. Ten nurses were individually interviewed in semi-structured interviews. The data were analysed using thematic analysis. Results: Three broad themes were identified, namely: (1) Emotional and informational support (2) Keeping the support going (3) Seeking help from others. The data provide insights into how nurses provide emotional and informational support to parents in the NICU setting. Challenges were encountered in providing support and were addressed through the involvement of the doctors and emotional support continuity by nursing colleagues. Conclusion: This paper describes two critical supports given to the parents in the NICU setting and the challenges that underline these supports and proposes strategies used by nurses to help the parents. The balance needed between work demand and parental support is highlighted. In order to give more robust parental support, ongoing interactions with doctors and nursing colleagues are required.